Identification of compounds with activity against Trypanosoma cruzi within a collection of synthetic nucleoside analogs - Barnadas-Carceller, Berta; Martinez-Peinado, Nieves; Gómez, Laura Córdoba; Ros-Lucas, Albert; Gabaldón-Figueira, Juan Carlos; Diaz-Mochon, Juan J.; Gascon, Joaquim; Molina, Ignacio J.; Pineda de las Infantas y Villatoro, María José; Alonso-Padilla, Julio (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Chagas disease is caused by the protozoan parasite Trypanosoma cruzi, and it is the most important neglected tropical disease in the Americas. Two drugs are available to treat the infection, but their efficacy in the chronic stage of the disease, when most cases are diagnosed, is reduced. Their tolerability is also hindered by common adverse effects, making the development of safer and efficacious alternatives a pressing need. T. cruzi is unable to synthesize purines de novo, relying on a purine salvage pathway to acquire these from its host, making it an attractive target for the development of new drugs. Methods We evaluated the anti-parasitic activity of 23 purine analogs with different substitutions in the complementary chains of their purine rings. We sequentially screened the compounds' capacity to inhibit parasite growth, their toxicity in Vero and HepG2 cells, and their specific capacity to inhibit the development of amastigotes. We then used in-silico docking to identify their likely targets. Results Eight compounds showed specific anti-parasitic activity, with IC50 values ranging from 2.42 to 8.16 μM. Adenine phosphoribosyl transferase, and hypoxanthine-guanine phosphoribosyl transferase, are their most likely targets. Discussion Our results illustrate the potential role of the purine salvage pathway as a target route for the development of alternative treatments against T. cruzi infection, highlithing the apparent importance of specific substitutions, like the presence of benzene groups in the C8 position of the purine ring, consistently associated with a high and specific anti-parasitic activity.